Determinants of prescribing decisions for off-patent biological medicines in Belgium: a qualitative study - Yannick Vandenplas; Steven Simoens; Philippe Van Wilder; Arnold G. Vulto; Florian Turk; Isabelle Huys (BMC, 2022)
Abstract Background A competitive market for off-patent biologicals leads to more affordable and high-quality healthcare. In recent years, Belgium has been characterized by its low use of biosimilars and by its shifts from off-patent biologicals toward new alternative therapies. Yet, the prescribing decisions involved in these observations are poorly understood. This study aims to better understand prescribing choices among Belgian physicians in the ambulatory care setting. Methods This study consisted of two phases. First, a scoping literature review to identify determinants of prescribing choices was conducted. Scientific databases (Embase and PubMed) were searched until 4 November 2021. Second, the nominal group technique (NGT) was employed during focus group discussions with Belgian physicians to consider and validate these determinants for off-patent biologicals in the Belgian context. The qualitative data resulting from the literature review and focus group discussions were analyzed using the thematic framework method. Results Fifty-three scientific articles that discussed elements that determine prescribing choices were identified. Out of these, 17 determinants of prescribing choices were found. These were divided into five categories: (1) product-related, (2) physicians' personal, (3) healthcare system-related, (4) patient-related, and (5) determinants related to the pharmaceutical company or brand. Nineteen Belgian physicians from different therapeutic areas that regularly prescribe biologicals then participated in focus group discussions. Using the NGT, the group discussions revealed that prescribing choices for off-patent biologicals are determined by a complex set of elements. Clinical data, geographical region, working environment, pharmaceutical marketing, patient profile, clinical guidelines, and preference of key opinion leaders (KOL) were considered most influential. Physicians indicated that the importance of these determinants differs depending on product classes or therapeutic domain. Conclusions Multiple elements determine the choice of an off-patent biological or biosimilar product. The importance of each of these determinants varies depending on the context in which the prescribing choice is made. To increase the prescription of best-value biologicals in the Belgian ambulatory care, a set of synergistic measures is required including information for healthcare providers (HCP) and patients, prescribing feedback, prescribing targets, tangible incentives, KOL involvement, guidelines regarding pharmaceutical promotion, and regular revision of reimbursement modalities.